Clinical characteristics of patients with snow sports trauma transported to a trauma care center: A retrospective observational study. Issue 5 (May 2023) - Yoshimura, Genki; Kamidani, Ryo; Yasuda, Ryu; Miura, Tomotaka; Yamaji, Fuminori; Mizuno, Yosuke; Kitagawa, Yuichiro; Fukuta, Tetsuya; Ishihara, Takuma; Suzuki, Kodai; Miyake, Takahito; Nagaya, Soichiro; et al.
Highlights: Falls after jumping, as the mechanism of injury, is associated with emergency surgery under general anesthesia. Snowboarders are significantly more likely than skiers to require emergency surgery under general anesthesia. To the best of our knowledge, this is the first study to analyze whether more urgent surgery is required for patients with snow sports trauma depending on the type of equipment and the mechanism of injury. Abstract: Background: Snow sports are a popular recreational activity; however, the incidence of injury of snow sports can be high for skiers and snowboarders. Our hospital receives severe trauma cases from snow resorts and hospitals throughout the region. This study aimed to determine whether the risk of snow sports-related major trauma that requires emergency surgery under general anesthesia varies by the equipment and injury mechanism. Methods: This retrospective cohort study included patients with snow sports trauma referred to Gifu University Hospital, Japan between November 2010 and March 2020. We analyzed the need for emergency operation under general anesthesia within 24 h using Fisher's exact test. We identified 106 patients: (1) 90 in the snowboarders' group and 16 in the skiers' group or (2) 46 in the fall after jumping group (jumping group), 27 in the collide with other people and obstacle group (collision group), and 33 in the fall during gliding group (gliding group). Results: Snowboarders were nearly twice as likely as skiers to require emergency surgery under general anesthesia (44% vs. 25%; p = 0.236]. No significant associations were found between emergency surgery under general anesthesia and injury mechanism, but half of the patients in the jumping group required emergency surgery. Conclusions: Snowboard as equipment and falls after jumping as a mechanism of injury tended to be associated with emergency surgery under general anesthesia, with no significant differences. In order to provide adequate resources for snow sports trauma, the cause of the patient's injury is strongly related to the urgency of the condition, and transport to a trauma center should be actively considered. Further studies are warranted with respect to the effects of personal protective equipment and skill level.